2005
DOI: 10.1186/1471-2334-5-102
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between human papillomavirus infection and bladder transitional cell carcinoma

Abstract: Background: To determine the association of human papillomavirus infection (HPV) and transitional cell carcinoma (TCC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 14 publications
1
49
0
2
Order By: Relevance
“…In bladder cancer group, we have found that HPV 18 was the most frequent type, both in tissue and in urine samples (22.2%). These results are in line with other previous reports (20). Moreover, we found HPV 45 both in tissue (18.6%) and in urine samples (13.9%).…”
Section: Discussionsupporting
confidence: 83%
“…In bladder cancer group, we have found that HPV 18 was the most frequent type, both in tissue and in urine samples (22.2%). These results are in line with other previous reports (20). Moreover, we found HPV 45 both in tissue (18.6%) and in urine samples (13.9%).…”
Section: Discussionsupporting
confidence: 83%
“…[10][11][12] However, in a study involving Iranian patients, HPV DNA was detected in slightly over 35% of urothelial neoplasia cases, and 81% of the viral strains identified were HPV type 18, which is considered a high-risk strain for the development of uterine cervical neoplasia. 34 More recently, Li et al 7 have also shown the presence of HPV infection in bladder cancer. They implicated HPV type 16, which is also considered a high-risk strain for the development of uterine cervical neoplasia.…”
Section: Resultsmentioning
confidence: 98%
“…Until now, conflicting findings have been reported on association between HPV infection and bladder carcinoma [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. In the present study, we analyzed urothelial bladder tumor samples for HPV in order to clarify the controversial role of HPV in bladder cancers.…”
Section: Introductionmentioning
confidence: 88%